Comparative Anatomical Study of the Species Notobasis syriaca Cass and Silybum marianum L. (Asteraceae) in Salah-Aldin Governorate (Iraq) - Abd, Ayman Adwan (Journal for Research in Applied Sciences and Biotechnology, 2023)
The species Notobasis syriaca Cass. and Silybum marianum L. among the most important endemic plants of the Asteraceae family in the Iraqi flora. The anatomy of the stem and leaves of both species was studied using a compound microscope, due to the similarity between the two species in many morphological characteristics and grow in the same environment. Therefore, this research work was conducted to find Anatomical differences of taxonomic value that help distinguish between the two species under study. Results concluded great importance for anatomical characteristics were achieved by studying stem cross section, leaf epidermis and leaf cross section for both species and compare the anatomical characteristics between the two species under study in a scientific manner.